Gender-based analysis of working-carer men: a North American scoping review. (23rd March 2018) - Maynard, Kevin; Ilagan, Chloe; Sethi, Bharati; Williams, Allison
Abstract : The purpose of this scoping review is to find all existing North American literature on male working carers and compare this information with female working carers. Searches were performed using various databases, published between 1996 and 2016. A total of 506 articles were found and 45 (n = 45) met all inclusion criteria. Five qualitative themes were identified: caregiving characteristics; motives for caring; work impacts; health impacts; and caring in the workplace and coping strategies. This review narrows the gap in the literature with respect to the similarities and differences between male and female working carers, and the way in which they approach caregiving tasks.